The Influence of Mobile Learning on Student Motivation in Remote Areas - Al-Mansour, Youssef; Al-Jawad, Khaled; Al-Nasser, Maha (Al-Hijr: Journal of Adulearn World, 2025)
Mobile learning has become a pivotal educational tool, especially in remote areas where access to traditional educational resources is limited. In these settings, mobile learning offers flexibility, accessibility, and the potential to engage students in their learning process. The influence of mobile learning on student motivation in remote areas, however, remains an area that has not been extensively studied. This research investigates the impact of mobile learning on student motivation in remote areas, aiming to understand how mobile devices and applications can improve student engagement, learning outcomes, and persistence in these regions. A mixed-methods approach was employed, combining quantitative surveys to measure student motivation and qualitative interviews to gather insights into the personal experiences of students and educators. The study involved 300 students from remote areas who used mobile learning tools over a semester. The results show a significant increase in student motivation, with 65% of students reporting greater engagement in learning activities. Students cited the flexibility, accessibility, and interactive nature of mobile learning as key factors that contributed to their motivation. This study concludes that mobile learning positively influences student motivation in remote areas, offering valuable opportunities for improving education in underserved regions. Mobile learning can be an essential tool in bridging educational gaps and fostering student engagement, even in challenging learning environments.